Identification of Clubroot-Resistant Germplasm in a Radish (Raphanus sativus L.) Core Collection - Yang Ma; Haiping Wang; Jiangping Song; Wenlong Yang; Huixia Jia; Niels Agerbirk; Yinan Chen; Chen Li; Yinglan Piao; Sen Li; Xiaohui Zhang (Agronomy, 2024)
Clubroot disease, caused by Plasmodiophora brassicae, poses a significant global threat to cruciferous crops. The epidemic area of clubroot disease is expanding rapidly. In response to this pressing issue, there is a compelling need for the development of clubroot disease-resistant radish cultivars. China boasts an extensive array of radish varieties and germplasm resources. However, a comprehensive assessment of their resistance to clubroot has not yet been carried out, thereby impeding the effective utilization of germplasm and clubroot-resistant breeding. Therefore, it is urgent to systematically evaluate the clubroot resistance of the radish germplasm and identify resistant resources. In this study, clubroot resistance evaluations were conducted on 268 excellent radish varieties derived from 30 provinces in China, as well as seven accessions from Russia, North Korea, France, South Korea, and Germany. The resistance evaluation revealed a diverse range of resistance indices, with a mean disease index (DI) ranging from 0.6 to 58.5, showing significant disparities in clubroot resistance among these radish resources. A total of six accessions were characterized as highly resistant to clubroot, and a further 50 accessions were characterized as resistant. The disease-resistant radishes showed diversity in horticultural traits. Provinces in South China contributed significantly more resistance germplasm than those of North China. These materials are of great value for both genetic investigation and the crop breeding of clubroot resistance. Furthermore, we employed a previously established clubroot-resistance-linked SSR marker to analyze the clubroot-resistant resources. The accessions exhibited dissimilar genetic profiles from known clubroot-resistant germplasm, suggesting their potential status as novel sources of clubroot resistance. Conclusively, these newly identified accessions enriched the genetic diversity within the clubroot-resistant gene pool and may contribute to the future cloning of previously undiscovered clubroot-resistant genes.